2021
DOI: 10.18632/oncotarget.27959
|View full text |Cite
|
Sign up to set email alerts
|

CEA as a blood-based biomarker in anal cancer

Abstract: Background: The clinical utility of a blood-based biomarker in squamous cell carcinoma of the anus (SCCA) is unknown. We analyzed carcinoembryonic antigen (CEA), a commonly employed assay for patients with colorectal adenocarcinoma, as a serum biomarker for patients with biopsy-proven SCCA. Materials and Methods: Medical records from 219 patients with biopsy-proven SCCA at the University of Texas MD Anderson Cancer Center were reviewed under an IRB-approved protocol from 2013 to 2020 to assess for correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Sadeghi et al found that CEA was a useful biomarker in characterizing SCC from basal cell carcinoma [34]. However, one study mentioned that although CEA was increased in anal cancer, but it did not have value in survival prediction, thus it is not a clinical biomarker for SCC [35]. Therefore, CEA is more useful in characterizing AD and SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Sadeghi et al found that CEA was a useful biomarker in characterizing SCC from basal cell carcinoma [34]. However, one study mentioned that although CEA was increased in anal cancer, but it did not have value in survival prediction, thus it is not a clinical biomarker for SCC [35]. Therefore, CEA is more useful in characterizing AD and SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Based on sequence homology, the CEA gene family can be separated into two subgroups: PSG and CEA ( Streydio et al, 1988 ). CEA has been extensively studied and used as a cancer marker ( Hester et al, 2021 ; Moretto et al, 2021 ; Taheri et al, 2022 ), whereas PSG, especially PSG7, has been relatively poorly studied in the field of oncology, ( Su et al, 2020 ). Unlike other PSGs, PSG7 is characterized by an unblocked N-terminus, which may indicate special biological functions worthy of further research ( Khan and Hammarström, 1990 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is limited by false-positive results in patients with in ammation and non-PCa lesions and false-negative results in Lewis-negative individuals. Likewise, the accuracy of the other blood-based biomarkers is not strong because of their non-speci c aberration in cancers other than PCa [11,12].…”
Section: Introductionmentioning
confidence: 99%